2016
DOI: 10.1007/s10460-016-9683-6
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture as an asset class: reshaping the South African farming sector

Abstract: According to portfolio managers, agriculture in general, and farmland in particular, can be considered an emerging asset class. Specialized financial vehicles, such as private equity and mutual funds, are emerging and competing to attract potential investment in this asset class. In recent years, there has been significant development of such vehicles targeting South Africa's farming sector. These innovations are led by a group of market intermediaries (e.g. asset managers or consultants) who endeavour to “re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…Even work that explores the financialization of farmland/agriculture in more detail (Dixon, 2013;Fairbairn, 2014;Gunnoe, 2014;McMichael, 2012;Sommerville, 2013) often does not escape this analytical gaze and usually makes use of a narrow range of authors (Arrighi, 2010(Arrighi, [1994; Epstein, 2005;Harvey, 2006Harvey, [1982; Krippner, 2005), whose take on financialization is largely compatible with a more structuralist political economy perspective. Many intriguing perspectives on money, finance, or the making of new markets in the fields of heterodox economics, cultural economy, the social studies of finance, the social studies of markets, economic geography and sociology have received little to no recognition in the existing literature (but see Ducastel and Anseeuw, 2014;Ouma, 2014;Williams, 2014). For instance, Fairbairn (2013Fairbairn ( , 2014, one of the pioneering authors, argues that, despite the claim of financial actors that investing into 'real things' sustained by market fundamentals represented a break with the practices of 'financial engineering' which had created the global economic turmoil (Colvin and Schober, 2012), the logics of financialization as practiced elsewhere were now simply being extended to farmland and agriculture (see also Russi, 2013).…”
Section: Dominant Imaginaries Associated With the Farmlandagriculturementioning
confidence: 99%
See 3 more Smart Citations
“…Even work that explores the financialization of farmland/agriculture in more detail (Dixon, 2013;Fairbairn, 2014;Gunnoe, 2014;McMichael, 2012;Sommerville, 2013) often does not escape this analytical gaze and usually makes use of a narrow range of authors (Arrighi, 2010(Arrighi, [1994; Epstein, 2005;Harvey, 2006Harvey, [1982; Krippner, 2005), whose take on financialization is largely compatible with a more structuralist political economy perspective. Many intriguing perspectives on money, finance, or the making of new markets in the fields of heterodox economics, cultural economy, the social studies of finance, the social studies of markets, economic geography and sociology have received little to no recognition in the existing literature (but see Ducastel and Anseeuw, 2014;Ouma, 2014;Williams, 2014). For instance, Fairbairn (2013Fairbairn ( , 2014, one of the pioneering authors, argues that, despite the claim of financial actors that investing into 'real things' sustained by market fundamentals represented a break with the practices of 'financial engineering' which had created the global economic turmoil (Colvin and Schober, 2012), the logics of financialization as practiced elsewhere were now simply being extended to farmland and agriculture (see also Russi, 2013).…”
Section: Dominant Imaginaries Associated With the Farmlandagriculturementioning
confidence: 99%
“…Strong concepts such as 'food security', 'accumulation by dispossession' or 'new enclosures' indicate such an orientation. This has been accompanied by a limited engagement with actors from the financial industry themselves (but see Ducastel and Anseeuw, 2014;Fairbairn, 2014), who may have something interesting to say, are often convinced they do good by contributing to global food security, and, as my own research has shown, are frequently distancing themselves from a ''Wall Street mentality'' applied to farming. This lack of engagement has resulted in grand narratives on 'bankers-turnedfarmers', without any more situated fieldwork -be it interviews or ethnography -sustaining them.…”
Section: Dominant Imaginaries Associated With the Farmlandagriculturementioning
confidence: 99%
See 2 more Smart Citations
“…A defining feature of economic restructuring over the last half century has been the corporate concentration of socioeconomic resources and their rendering as tradeable income‐streams—a process Birch (, ) terms “assetisation” (see also Ducastel and Anseeuw , ; Ignatova ; Nally ). Assetisation is a principal component of financialisation and an important material mechanism driving neoliberalisation.…”
mentioning
confidence: 99%